Preparation method of sheet-like polyimide porous material

Through the method of drying the legal system, the high -power electromagnetic shock wave generator uses the fibrosis of the bonding agent, and the porous structure is formed through the thermal pressure and thermal treatment. The high pore rate, thermal conductivity and mechanical strength of pores.

CN112457668BActive Publication Date: 2025-01-28NORTH & SOUTH BROTHER PHARMACY INVESTMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011229692.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-06
Publication Date
2025-01-28
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

The existing preparation methods of sheet-shaped polyimide porous materials have problems such as complex process, high cost and long production cycle, which lead to limited application.

Method used

The method of preparing method of dry method is used to mix the polyanide powder, thermal conductivity and adhesive, and fibrilize the binder in the high -power electromagnetic shock wave generator, and then perform thermal pressure and heat treatment to remove the catalyst to form formation Pores.

Benefits of technology

The obtained chip -shaped polytamide polymidomial materials have high pore rate, good thermal conductivity and mechanical strength, and are suitable for aviation aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002764768180000071
    Figure BDA0002764768180000071
  • Figure BDA0002764768180000081
    Figure BDA0002764768180000081
Patent Text Reader

Abstract

The present invention provides a method for preparing a sheet-like polyimide porous material, comprising: mixing polyimide powder, a thermal conductive filler, and a binder, and then transferring the mixed material into a high-power electromagnetic shock wave generator to fiberize the binder to form a first mixed material; mixing the first mixed material with a first catalyst and a second catalyst to obtain a second mixed material; hot pressing the second mixed material to deagglomerate the first catalyst under the action of the second catalyst to form a sheet-like film; heat treating the sheet-like film to remove the first catalyst and the second catalyst to obtain a sheet-like polyimide porous material. The sheet-like polyimide porous material prepared by the present invention has high porosity, excellent mechanical properties and thermal conductivity, and is expected to be used in the aerospace field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyimide material preparation, and in particular to a method for preparing a sheet-like polyimide porous material. Background Art

[0002] Thin sheet porous material is a planar material with a network structure consisting of interconnected or closed holes, and the boundaries or surfaces of the holes are composed of pillars or flat plates. Unlike film materials with a thickness of ≤0.1mm, the thickness of thin sheet porous materials can range from 0.1 to 5mm, also known as coiled materials. Due to its thickness advantage, thin sheet porous materials have the advantages of light weight, low relative density, high specific strength, high specific surface area, sound insulation, heat insulation, and good permeability.

[0003] Compared with traditional porous materials, thin-sheet polyimide porous materials have broad application prospects and development space in the fields of aerospace, navigation, etc. due to their characteristics of light weight, insulation, sound absorption, heat insulation, radiation resistance, flame retardancy, and ultra-thinness. The molding processes of thin-sheet polyimide porous materials mainly include solvent swelling method, powder microwave foaming method, supercritical CO2 method, electrospinning method, needle punching method, etc., but they all have corresponding disadvantages.

[0004] After the solvent swelling method is completed, the film can only be partially imidized, the foaming degree is low, the solvent boiling point is high, and it is difficult to remove; the powder microwave foaming method has a complex process flow and high cost; the supercritical CO2 method has a long production cycle, a complex process flow, complex equipment, and cannot be mass-produced; although the electrospinning method has been industrialized, the production cost is high; the needle punching method has a long preparation process flow, a long production cycle, and high cost, and still needs further optimization.

[0005] Therefore, the existing preparation method of sheet-like polyimide porous materials still needs to be improved. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a novel dry method for preparing a sheet-like polyimide porous material. The method is simple in process, and the obtained polyimide porous material has the advantages of high porosity, good heat resistance and heat dissipation, high mechanical strength, etc.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In one aspect, the present invention provides a method for preparing a sheet-like polyimide porous material, comprising:

[0009] (1) mixing polyimide powder, thermal conductive filler, and binder, and then transferring the mixed material into a high-power electromagnetic shock wave generator to fiberize the binder to form a first mixed material;

[0010] (2) mixing the first mixed material with the first catalyst and the second catalyst to obtain a second mixed material;

[0011] (3) hot pressing the second mixed material so that the first catalyst is deagglomerated under the action of the second catalyst to form a sheet-like film;

[0012] (4) The sheet-like film is subjected to heat treatment to remove the first catalyst and the second catalyst, thereby obtaining a sheet-like polyimide porous material.

[0013] According to the preparation method of the sheet-like polyimide porous material provided by the present invention, on the one hand, the first catalyst is conducive to the processing of the polyimide powder into a thin film, and at the same time, through the action of the second catalyst, the first catalyst undergoes a depolymerization reaction and is finally removed under a high temperature environment, thereby finally forming a relatively rich porous structure in the sheet-like polyimide material.

[0014] The polyimide can withstand high temperatures above 300°C, and its specific structure is not particularly limited. Preferably, it is an aromatic polyimide, which has excellent high temperature resistance. The polyimide powder can be purchased directly or prepared by itself. The preparation method can be any method known in the art, for example, aromatic dianhydride and aromatic diamine can be reacted to obtain a polyimide precursor solution, and then chemical imidization can be performed to obtain polyimide powder.

[0015] The aromatic dianhydride may be selected from one or more of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), diphenyl ether tetracarboxylic dianhydride (ODPA), and biphenyl sulfone tetracarboxylic dianhydride (DSDA), but is not limited thereto.

[0016] The aromatic diamine is selected from one or more of 3,4'-diaminodiphenyl ether (3,4'-ODA), 4,4'-diaminodiphenyl ether (4,4'-ODA), m-phenylenediamine (m-PDA), p-phenylenediamine (p-PDA), 4,4'-diaminodiphenylmethane (MDA), 4,4'-diaminodiphenyl sulfone (DDS), 3,3'-diaminodiphenyl sulfone (3,3'-DDS), and 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFDB), but is not limited thereto.

[0017] According to some embodiments provided by the present invention, the thermally conductive filler is at least one of aluminum oxide, aluminum nitride, boron nitride, and silicon carbide. The particle size of the thermally conductive filler is preferably 0.1-10 μm.

[0018] The bonding of the present invention forms a strong three-dimensional network system between the polyimide powder, the thermal conductive filler and the adhesive through fiberization, which can avoid the agglomeration of the thermal conductive filler and make it evenly and firmly dispersed in the polyimide matrix.

[0019] According to some embodiments provided by the present invention, the binder is at least one of polytetrafluoroethylene and ultra-high molecular weight polyethylene.

[0020] According to some embodiments provided by the present invention, the condition for causing the binder to undergo fiberization is: setting the impact pressure of the high-power electromagnetic shock wave generator to 5-10 MP and the impact frequency to 10-30 Hz.

[0021] The present invention uses a high-power electromagnetic shock wave generator to fiberize the binder, and the fiberization is more thorough, so that a strong three-dimensional network system is formed between the polyimide, the thermally conductive filler, and the binder, which can avoid the agglomeration of the thermally conductive filler and make it evenly and firmly dispersed in the polyimide matrix. While improving the thermal conductivity, it can give the sheet-like polyimide porous material a strong physical strength and a large elastic modulus, thereby improving its mechanical properties.

[0022] According to some embodiments provided by the present invention, the mass ratio of the polyimide, the thermal conductive filler, and the binder is 100:1-10:1-20, preferably 100:3-8:5-15.

[0023] Specifically, the mass ratio of the polyimide, the thermal conductive filler, and the adhesive can be listed as: 100:3:5, 100:3:8, 100:3:10, 100:5:5, 100:5:8, 100:5:10, 100:5:15, 100:8:8, 100:8:10, 100:8:15, 100:5:15, and the like.

[0024] The first catalyst of the present invention can be deagglomerated under the action of the second catalyst and removed by high-temperature heating, thereby forming pores.

[0025] According to some embodiments provided by the present invention, the first catalyst is at least one of polypropylene carbonate, polyethylene carbonate, polyvinyl chloride, and polycarbonate.

[0026] Preferably, the viscosity average molecular weight of the polycarbonate is 3000 to 20000. According to some embodiments provided by the present invention, the viscosity average molecular weight of the polycarbonate is 3000 to 15000.

[0027] The material state of the first catalyst can be liquid or solid according to the degree of polymerization. When the state of the first catalyst can be both solid and liquid, preferably, the liquid first catalyst and the solid first catalyst are mixed and used, and the mass ratio of the two can be any ratio.

[0028] According to some embodiments provided by the present invention, the first catalyst is polypropylene carbonate, preferably a mixture of solid polypropylene carbonate (PPC-liq) and liquid polypropylene carbonate (PPC-sol).

[0029] When the first catalyst is a mixture of liquid polypropylene carbonate and solid polypropylene carbonate, the mass ratio of the two can be any ratio.

[0030] According to some embodiments provided by the present invention, the second catalyst is at least one of aniline, 1-naphthylamine, N,N′-dibutylaniline, N,N′-dimethylaniline, ethylamine, ethylenediamine, triethanolamine, and tri-n-butylamine, preferably triethanolamine.

[0031] According to some embodiments provided by the present invention, the mass ratio of the first mixed material to the first catalyst is 100:10 to 80, preferably 100:50 to 70. If the amount of the first catalyst is too large, the strength of the sheet-like polyimide porous material will decrease; if the amount of the first catalyst is too small, the porosity of the obtained sheet-like polyimide porous material is not ideal.

[0032] According to some embodiments provided by the present invention, the mass ratio of the first catalyst to the second catalyst is 1:0.1 to 0.5, preferably 1:0.1 to 0.3. If the amount of the second catalyst is too small, the first catalyst is not fully deagglomerated, which is not conducive to the formation of a porous structure; if the amount of the second catalyst is too large, there is a risk of incomplete removal.

[0033] According to some embodiments provided by the present invention, the hot pressing temperature is 40° C. to 100° C., preferably 60° C. to 100° C. If the hot pressing temperature is too high, the first catalyst and the second catalyst may be removed prematurely, and the process is out of control.

[0034] According to some embodiments provided by the present invention, the hot pressing rate is 0.5-5 m / min or 0.5-3 m / min, preferably 0.5-1 m / min. If the hot pressing rate is too high, the mixed material will not be heated sufficiently, which is not conducive to the full fiberization and curing of the binder, and is not conducive to the full deagglomeration of the first catalyst.

[0035] In some embodiments provided by the present invention, the thickness of the film obtained by hot pressing is 0.1-1 mm.

[0036] According to some embodiments provided by the present invention, the temperature of the heat treatment is 100° C. to 400° C. or 100° C. to 350° C., preferably 180° C. to 300° C. The heat treatment temperature is preferably such that the first catalyst and the second catalyst are completely removed. If the temperature is too low, the first catalyst and the second catalyst may not be fully removed, affecting the subsequent use effect of the material.

[0037] According to some embodiments provided by the present invention, the heat treatment time is 0.1-2 hours, preferably 0.1-1 hour.

[0038] The sheet-like polyimide porous material obtained by the above preparation method has a rich pore structure, preferably, the sheet-like polyimide porous material has a porosity of more than 40%, more preferably, a porosity of more than 50%. According to some embodiments provided by the present invention, the porosity of the sheet-like polyimide porous material is 40%-90%.

[0039] The sheet-like polyimide porous material prepared by the invention has high porosity, excellent mechanical properties and thermal conductivity, and good bonding property, and is suitable for use in the aerospace field.

[0040] Compared with the prior art, the present invention has the following technical effects:

[0041] (1) The present invention uses a high-power electromagnetic shock wave generator to fiberize the binder, which makes the fiberization more thorough and forms a strong three-dimensional network system among the polyimide, the thermal conductive filler and the binder, and solidifies them through the action of a hot roller press, thereby avoiding the agglomeration of the thermal conductive filler and making it evenly and firmly dispersed in the polyimide matrix. While improving the thermal conductivity, the sheet-like polyimide porous material is endowed with strong physical strength and a large elastic modulus.

[0042] (2) The present invention introduces a first catalyst during the preparation process of the sheet-like polyimide porous material. The first catalyst can be deagglomerated under the action of the second catalyst and removed by high-temperature heating to form pores, thereby obtaining a sheet-like polyimide porous material with a porous structure. The process is simple and environmentally friendly, and is suitable for industrial production.

[0043] (3) The sheet-like polyimide porous material provided by the present invention has high porosity, excellent mechanical properties and thermal conductivity, and good adhesion, and is expected to be used in the aerospace field. DETAILED DESCRIPTION

[0044] Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. All patents and publications related to the present invention are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, that is, including the contents specified in the present invention, but does not exclude contents in other aspects.

[0045] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification or the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] The polyimide powder described in the embodiment of the present invention is obtained by reacting PMDA with 4,4'-ODA.

[0047] Example 1

[0048] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0049] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:50:5 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0050] Example 2

[0051] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0052] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:50:15 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0053] Example 3

[0054] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0055] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:60:6 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0056] Example 4

[0057] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0058] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:70:21 using a high-speed mixer to obtain a second mixed material; the mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0059] Example 5

[0060] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0061] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed uniformly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed uniformly with polycarbonate (viscosity-average molecular weight is 5000) and triethanolamine at a mass ratio of 100:50:5 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polycarbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0062] Example 6

[0063] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0064] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:50:5 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 180°C for heat treatment for 1h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0065] Comparative Example 1

[0066] This comparative example provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0067] Polyimide powder, aluminum nitride, and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to a high-power electromagnetic shock wave generator, and the impact pressure is set to 8MPa and the impact frequency is set to 30Hz, so that the ultra-high molecular weight polyethylene powder is fully fiberized to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate at a mass ratio of 100:50 using a high-speed mixer to obtain a second mixed material; the second mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a diaphragm with a thickness of 0.5mm; the diaphragm is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to obtain a sheet-like polyimide porous material.

[0068] Comparative Example 2

[0069] This embodiment provides a method for preparing a flexible sheet-like polyimide porous material with a porous structure, comprising the following steps:

[0070] Polyimide powder, aluminum nitride and ultra-high molecular weight polyethylene powder are mixed evenly in a three-dimensional mixer at a mass ratio of 100:5:10, and then the mixed materials are transferred to an air flow pulverizer for air flow pulverization to obtain a first mixed material; the first mixed material is mixed evenly with polyvinyl carbonate and triethanolamine at a mass ratio of 100:50:5 using a high-speed mixer to obtain a second mixed material; the mixed material is rolled using a hot roller press at a roller surface temperature of 80°C and a rolling rate of 1m / min to form a membrane with a thickness of 0.5mm; the membrane is placed in a high-temperature oven at 250°C for heat treatment for 0.5h to completely remove the depolymerized polyvinyl carbonate and triethanolamine to obtain a sheet-like polyimide porous material.

[0071] Performance Testing

[0072] The sheet-like polyimide porous materials prepared in the examples and comparative examples were subjected to thermogravimetric analysis, porosity, mechanical strength and thermal conductivity tests. The results are shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] It can be seen from the data in Table 1 that the sheet-like polyimide porous material obtained in the embodiment of the present invention has a porosity of up to 80-90%, a thermal conductivity of more than 50, a tensile strength of more than 2.7 MPa, an elongation of more than 150%, and excellent comprehensive performance. However, since no second catalyst is added to Comparative Example 1, the first catalyst cannot be fully deagglomerated and is not fully removed, the porosity is small, and except for the tensile strength, other properties have decreased to varying degrees. Since Comparative Example 2 uses a general airflow pulverization, the fiberization effect of the binder is relatively poor, the dispersion effect of the thermal conductive filler is poor, and the bonding force with the polyimide is reduced, resulting in poor comprehensive performance of the product, especially the mechanical properties.

[0077] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0078] Although the embodiments and examples of the present invention have been shown and described above, it is to be understood that the above embodiments and examples are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments and examples within the scope of the present invention.

Claims

1. A method for preparing a sheet-like polyimide porous material, characterized in that: include: (1) mixing polyimide powder, thermal conductive filler, and binder, and then transferring the mixed material into a high-power electromagnetic shock wave generator to fiberize the binder to form a first mixed material; The binder is at least one of polytetrafluoroethylene and ultra-high molecular weight polyethylene; The conditions for causing the binder to undergo fiberization are: setting the impact pressure of the high-power electromagnetic shock wave generator to 5-10 MP and the impact frequency to 10-30 Hz; (2) mixing the first mixed material with the first catalyst and the second catalyst to obtain a second mixed material; The first catalyst is at least one of polypropylene carbonate, polyethylene carbonate, polyvinyl chloride, and polycarbonate; The second catalyst is at least one of aniline, 1-naphthylamine, N,N'-dibutylaniline, N,N'-dimethylaniline, ethylamine, ethylenediamine, triethanolamine, and tri-n-butylamine; (3) hot pressing the second mixed material so that the first catalyst is deagglomerated under the action of the second catalyst to form a sheet-like film; (4) The sheet-like film is subjected to heat treatment to remove the first catalyst and the second catalyst, thereby obtaining a sheet-like polyimide porous material.

2. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The thermal conductive filler is at least one of aluminum oxide, aluminum nitride, boron nitride and silicon carbide.

3. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The mass ratio of the polyimide powder, the thermal conductive filler and the adhesive is 100:1-10:1-20.

4. The method for preparing a sheet-like porous polyimide material according to claim 1, characterized in that: The mass ratio of the first mixed material to the first catalyst is 100:50-70.

5. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The mass ratio of the first catalyst to the second catalyst is 1:0.1-0.

5.

6. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The hot pressing temperature is 40°C to 100°C.

7. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The hot pressing rate is 0.5-5 m / min.

8. The method for preparing a sheet-like porous polyimide material according to claim 1, characterized in that: The temperature of the heat treatment is 100°C to 400°C.

9. The method for preparing a sheet-like polyimide porous material according to claim 1, characterized in that: The heat treatment time is 10-40 minutes.

10. The sheet-like polyimide porous material obtained according to the preparation method according to any one of claims 1 to 9.

11. Application of the sheet-like polyimide porous material according to claim 10 in the field of aerospace.

Citation Information

Patent Citations

  • Auxiliary control method for polystyrene polymerization by pulse electromagnetic fields

    CN104448072A

  • Porous electrode plate, preparation method thereof and capacitor

    CN108470648A